Pengaruh Pelat Penyerap terhadap Kinerja Solar Still di Kota Ngabang - Astrada, Astrada; Soeparman, Sudjito; Hamidi, Nurkholis (Jurnal Rekayasa Mesin, 2020)
The purpose of this study was to determine the effect of the use of black paint and gravel as an absorbent plate on solar still performance. This research was conducted to overcome the problem of limited clean water in the city of Ngabang, West Borneo. The research method used in this study is a direct experimental method for the object under study. Tests carried out on two solars still with a variety of absorbent plates, namely concrete coated with black paint and concrete coated with gravel. Surya is still made to have the same covering glass geometry. The duration of observation is 13 hours. Data collection is carried out every 10 minutes, starting at 06.00Â  until 19.00 local time. The results showed that concrete coated with gravel has higher performance compared to concrete coated with black paint as an absorbent plate on solar still. In the solar still, with gravel absorbent plates, the volume of distilled water is 3.64 L / 13 hours, and efficiency is 43.93%. Meanwhile, solar still coated with black paint as an absorbent plate producing a water volume of 2.42 L / 13 hours and an efficiency of 29.32%. The longer the observation time the sun's performance is still with gravel variations as an absorbent plate, the better it is compared to those who use black paint.